Cognitive biases under the perspective of agency theory. A proposal for a model (Revista Científica Compendium, 2018)
The following paper of theoretical-descriptive nature aims to present a proposal for the construction of a cognitive bias model in the principal-agent relationship, under the agency theory perspective. Its purpose was to make easier the comprehension of the behaviors of the principal and the agent in the performance of their activities in the organizational field. The subject was addressed from a bibliographic revision of the agency theory and the cognitive theory of the organization, selecting the proposed scheme of Makridakis (1990). It is presented as an input, a set of cognitive-bias relationships that can be applied work-wise. They can be susceptible of empirically proven and, therefore, they are useful in the making of the respective model.
Keywords: Agency theory; cognitive biases; principal-agent relationship